2011
DOI: 10.1111/j.1365-2362.2011.02625.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of kaerophyllin against liver fibrogenesis in rats

Abstract: Our results demonstrated that kaerophyllin protected the rat liver from TAA-caused injury and fibrogenesis by suppressing hepatic inflammation and inhibiting HSC activation, possibly through upregulation of PPAR-γ expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that many natural compounds derived from herbs can reduce the severity of hepatic fibrosis in vivo and in vitro (Lee et al, 2012;Wang et al, 2010;Yu et al, 2012). Hydroxysafflor yellow A (HSYA) is an active ingredient of the herb Carthamus tinctorius L. (Asteraceae) (safflower) (Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that many natural compounds derived from herbs can reduce the severity of hepatic fibrosis in vivo and in vitro (Lee et al, 2012;Wang et al, 2010;Yu et al, 2012). Hydroxysafflor yellow A (HSYA) is an active ingredient of the herb Carthamus tinctorius L. (Asteraceae) (safflower) (Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic PPARγ ligands such as 15d-PGJ2 and all-trans retinoic acid (ATRA) inhibited the pro-fibrogenic and pro-inflammatory effects of HSCs (Sharvit et al 2013). In addition, kaerophyllin, a lignan, isolated from traditional Chinese herbs, up-regulated PPARγ expression, inhibited HSC activation in vitro, and protected rat livers from TAA-induced injury and fibrogenesis by inhibiting liver inflammation (Lee et al 2012). A clinical trial indicated that PPARγ-agonists thiazolidinediones significantly improved lobular inflammation, steatosis, and inflammation in patients with NASH (Boettcher et al 2012).…”
Section: Down-regulating Myofibroblast Activation and Ecm Productionmentioning
confidence: 97%
“…For example, intraperitoneal injection of TAA for 6 weeks increased fibrous septa, portal tract, and liver sinusoids as well as α -SMA staining of liver cells, the same as in the CCl 4 model. In the TAA model, administration of kaerophyllin from Bupleurum scorzonerifolium reversed histopathological changes and further reduced the levels of proinflammatory cytokines TNF- α , IL-1 β , and MCP-1 [ 34 ].…”
Section: Animal Models For Liver Fibrosis and Cirrhosismentioning
confidence: 99%